Peran Bimbingan dan Konseling Islam dalam Mencegah Pergaulan Bebas Remaja di Desa Timbang Lawan - Wahyuni, Sri; Ramadhani, Adeliya; Sahara, Annisa; Sagala, Ismaniar Hasanah; Sahfitri, Rani (Al-Ittizaan: Jurnal Bimbingan Konseling Islam, 2024)
This study aims to examine the role of Islamic guidance and counseling in preventing adolescent deviant behavior in Timbang Lawan Village. The phenomenon of deviant behavior among adolescents has been increasing, ranging from delinquency, drug abuse, and violence to other forms of misconduct that can disrupt their moral and spiritual development. This research employs a qualitative approach with a case study method. The methods utilized in this approach include observation, interviews, and document analysis. The results of this study reveal that Islamic guidance and counseling play a significant role in preventing deviant behavior and misconduct among adolescents by providing understanding of moral values, enhancing spiritual awareness, and strengthening their relationship with religion. Through the approach of Islamic guidance and counseling, religious values are applied to shape better character in adolescents. Islamic guidance and counseling have proven effective in helping adolescents overcome emotional and social problems, as well as providing them with guidance on living a life aligned with religious teachings. Thus, Islamic guidance and counseling can serve as a strategic effort in fostering adolescent morality amidst the challenges of modernization.